Machine learning‐assisted performance analysis of organic photovoltaics - Sijing Zhong; Jiayi Huang; Hengyu Meng; Zhuo Feng; Qianyue Wang; Zhenyu Huang; Lijie Zhang; Shiwei Li; Weiyang Gong; Yusen Huang; Lei Ying; Ning Li (Materials Genome Engineering Advances)
Abstract Although the power conversion efficiency of organic solar cells (OSCs) has been rapidly improved, there is still a lot of room for designing and developing new materials and their combinations to approach the efficiency limit. In this work, we establish a database of ∼100 bulk heterojunction OSCs composed of representative donors and acceptors reported in the literature, and train machine learning models to identify the efficiency potential of donor‐acceptor combinations. We find that the fully connected neural network achieves a Pearson coefficient of up to 0.88 for predicting the efficiency of OSCs with different combinations of donors and acceptors. We use sure independence screening and sparsifying method with feature analysis to analyze and evaluate the performance of OSCs. To prove the reliability and viability of the predictive model, we introduce the theoretical efficiency limits and confidence tests into the process, which provides a simple but reliable solution to quickly analyze and evaluate the potential of OSC materials and material combinations.